Sigorta sözleşmelerinde haksız şart ve genel işlem koşulu denetimi - Erkan, Emine Ebru (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Control of unfair terms and general conditions of contracts in insurance contracts